Effect of production costs and marketing costs on the net profits of consumer goods companies in Indonesia - Afif Haekhal (Institute of Computer Science (IOCS), 2022)
The purpose of this study was to examine the effect of production costs and marketing costs on the net profit of the cigarette sub-sector companies in Indonesia. The population in this study are all cigarette sub-sector companies in Indonesia, both those that have been listed on the Stock Exchange and those that have not. The samples used in this study were the three largest cigarette companies in Indonesia, namely PT Gudang Garam Tbk, PT Karya Dibya Mahardika (Apache), and PT Sampoerna Tbk. The data used in this study is primary data in the form of data on production costs, marketing, and net income for the early 2016-2020 period which is taken quarterly. The data analysis technique in this study used multiple linear regression. The results showed that production costs and operating costs simultaneously affect net income.